Advances in in vitro oocyte generation from pluripotent stem cells and ovarian stem cells - Mingxin Tian; Mingxin Tian; Meixiang Zhang; Meixiang Zhang (Frontiers in Endocrinology, 2025)
Reproductive cells play a crucial role in transmitting genetic and epigenetic information from one generation to the next. Oocytes are fundamental to reproduction but human oocytes are difficult to obtain for clinical and research purposes because of ethical restrictions. However, in vitro induction systems have been established to differentiate pluripotent stem cells (PSCs) into human primordial germ cells (hPGCs). These induced hPGCs are referred to as hPGC-like cells. The discovery of ovarian stem cells (OSCs) also opened up a new avenue for studying the development of germline stem cells. In this review, we discuss the latest advances in the development of oocytes in vivo and in vitro, involving PSC-derived PGCs and ovary-isolated OSCs. Specifically, we focus on induction methods and differentiation mechanisms and discuss the associated technical challenges and future directions.